Evaluation of Physicochemical Stability and Antioxidant Activity of Single Black Garlic Extract Capsules: Initial Development of Herbal Preparations - Ananta, I Gusti Bagus Teguh; Anggara, I Gede Yudi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Black garlic is a fermented product of fresh garlic that is rich in bioactive compounds such as S-allyl cysteine (SAC), polyphenols, and melanoidins, which play an important role as antioxidants and have the potential to be developed as supplements for preventing degenerative diseases. This study aims to evaluate the physicochemical stability and antioxidant activity of black garlic extract capsules during three months of accelerated storage (40 ± 2 °C; RH 75 ± 5%). Black garlic extract was obtained through ethanol maceration, concentration, and freeze-drying, and then formulated into capsules with amylum manihot and starch mucilage as excipients. The analyzed parameters included organoleptic characteristics, weight uniformity, moisture content, pH, total phenolic content using the Folin–Ciocalteu method, and antioxidant activity using the DPPH method. The results showed that capsule weight uniformity met pharmacopeia requirements throughout storage, while moisture content gradually increased, and pH showed a moderate decrease. Total phenolic content significantly decreased from 57.20 ± 0.92 to 43.40 ± 0.75 mg GAE/g by the third month. The antioxidant activity remained in the strong category, as indicated by an increase in IC50 values. The novelty of this study lies in its comprehensive evaluation of the stability of a single black garlic capsule product under accelerated conditions and its relationship to changes in bioactivity during storage. Overall, this study confirms that the single black garlic extract capsule product has good physicochemical stability and antioxidant activity, and has the potential to be developed as a herbal product with antioxidant capacity that is maintained and even increases during storage.